PERENCANAAN INSTALASI LISTRIK GEDUNG WAREHOUSE PT. XYZ SEMARANG JAWA TENGAH - Sumarno, Edy; Irawati, Irawati; Gazali, Ria (JEIS: Jurnal Elektro dan Informatika Swadharma, 2024)
Warehouse Building PT. XYZ at Semarang Central Java is a building place for keeping logistics owned by the company with a large area. There is also buildings' support in it so that required system installation suitable electricity with applicable standards such as PUIL 2011 and other standards in the field of electricity. The main electricity supply uses a source from PLN, and the generator is set as a backup source when electricity from PLN is dead. Plan installation at PT. XYZ Warehouse building, namely the installation of lighting, socket installation, air conditioning installation, electronics installation, installation of rolling door, installation of local government fire pump, and installation of clean water transfer pump. There are LVMDP panels, SDP panels, and subpanels as supply power for the installation that will be installed. Breaker rating selection power and dimensions cable delivery person who will use will affect on reliability network installation. Calculation of CRC will influence election breaker power, cable diameter selection delivery, and drop the voltage to happen on the network installation. The calculation was conducted manually. With more formerly collected load data equipment electricity at PT. XYZ Semarang and classification distribution system split panel installation, SDP panel, and LVMDP panel. The total load installed on the PT. XYZ Semarang Warehouse building is known as 318,406 VA or 318 kVA so the needed splicing power from PLN using customer of 329 kVA with use transformer with 400 kVA capacity and required generator set capacity of 400 kVA. The load on the LVMDP panel is 254,725 watts with KHA 569 A, so using MCCB with a rating of 630 A, using cable 7 x NYY 1c x 185 mm 2 with drop voltage 7.47 Volts or by 1.96% on the network 3 phase system. By PUIL 2011 standard decline voltage maximum of 4% so that the drop in the voltage on the LVMDP panel is still by the required standard.Gedung Warehouse PT.XYZ Semarang Jawa Tengah merupakan gedung yang berfungsi sebagai tempat untuk menyimpan logistik milik PT.XYZ dengan skala besar dimana terdapat juga banguan-bangunan penunjang di dalamnya, sehingga diperlukan sistem instalasi listrik yang sesuai dengan standar yang berlaku seperti PUIL 2011 dan standar lainnya dibidang kelistrikan. Supply listrik utama menggunakan sumber dari PLN, generator set digunakan sebagai sumber cadangan ketika listrik dari PLN mati. Rencana instalasi pada Gedung Warehouse PT.XYZ yaitu instalasi penerangan, instalasi stop kontak, instalasi tata udara, instalasi elektronik, instalasi rooling door, instalasi pompa pemdam kebakaran dan instalasi pompa transfer air bersih. Terdapat panel LVMDP, panel SDP dan panel Sub sebagai supply daya untuk instalasi yang akan dipasang. Pemilihan rating pemutus daya dan dimensi kabel penghantar yang akan digunakan akan berpengaruh pada keandalan jaringan instalasi. Perhitungan KHA akan mempengaruhi pemilihan pemutus daya, pemilihan diameter kabel penghantar dan penurunan tegangan yang akan terjadi pada jaringan instalasi. Perhitungan dilakukan secara manual. Dengan terlebih dahulu mengumpulkan data beban paralatan listrik pada Gedung Warehouse PT. XYZ Semarang dan klasifikasi pembagian sistem instalasi panel pembagi, panel SDP dan panel LVMDP. Beban total terpasang pada gedung Warehouse PT.XYZ Semarang diketahui sebesar 318.406 VA atau 318 kVA sehingga dibutuhkan penyambungan daya dari PLN menggunakan langganan sebesar 329 kVA dengan menggunakan transformator dengan kapasitas 400 kVA dan kapasitas generator set yang dibutuhkan sebesar 400 kVA. Beban pada panel LVMDP sebesar 254.725 watt dengan KHA 569 A sehingga menggunakan MCCB dengan rating 630 A, menggunakan kabel 7 x NYY 1c x 185Â  mm2 dengan penurunan tegangan sebesar 7.47 Volt atau sebesar 1,96 % pada jaringan sistem 3 fasa. Sesuai standar PUIL 2011 penurunan tegangan maksimal 4% sehingga penurunan tegangan pada panel LVMDP masih sesuai standar yang dipersyaratkan.